Proposição de equação para estimativa da sobrepressão máxima resultante de fechamento de válvulas de controle de fluxo - Viana, David Arruda (2024)
This study aims to develop a methodology for calculating the maximum surge pressure caused by the closure of flow control valves in gravity pipeline systems operating without the use of pumps. To achieve this, the creation of an equation is proposed that considers the effects of variables such as reservoir head, pipe thickness, total length, cross-sectional area, flow rate, valve closing time, wave celerity, and friction factor. The multiple linear regression technique was used to create the first pre-sizing equation and, subsequently, computational simulations of hydraulic transients were carried out using the UFC7 software, which allowed the analysis of overpressures in different scenarios and with different types of valves. and closing times. However, to formulate the second proposed equation, trial optimization was used. The methodology applied included the collection of data from published experiments and the modeling of hydraulic transients in UFC7, considering an upstream reservoir and a downstream valve. The simulations accounted for the elastic properties of the pipeline and specific boundary conditions to ensure accurate results. The study highlights that the choice of valve type and variations in closing time are critical factors that directly influence pressure peaks during hydraulic transient events. It was found that longer closing times significantly reduce maximum surge pressures, while valves with more gradual closing characteristics demonstrate greater capacity to attenuate the effects of water hammer. The results indicated that the proposed equations presented a good correspondence with the experimental data, allowing an efficient pre-sizing of the maximum overpressure considering the range of experimental data. This tool facilitates operational analysis and planning, offering a practical and quick solution for designers and operators aiming to minimize transient impacts in pipeline systems. Comparisons with values calculated using the Method of Characteristics (MOC and MOC_CAV) and experimental data demonstrated that the formulated equation provides reliable estimates, particularly for shorter closing times, making it ideal for applications requiring a rapid and dependable response. Despite its advantages, the analysis also revealed limitations for longer closing times in the first proposed equation. As for the second proposed equation, the results were close to those simulated in UFC7. Therefore, it is suggested that future research explore the expansion of the experimental database and simulations under different operational conditions. It is recommended to develop new equations that consider a broader variation in closing time parameters and the analysis of minimum surge pressures, aiming to provide a more comprehensive and detailed assessment of hydraulic systems. The use of more advanced algorithms, such as genetic algorithms, to improve model accuracy is also proposed for future studies. Thus, this study contributes to the safety and optimization of operations in water supply systems, providing a practical tool to address challenges related to hydraulic transients.